Optimization of multiplex real-time RT-PCR for respiratory syncytial viruses detection - Agustiningsih Agustiningsih (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
Abstract Background: Multiplex real-time RT-PCR (rRT-PCR) is a fast, sensitive and specific test to detect more than one target in single PCR reaction. In this study we developed multiplex rRT-PCR for RSV-A and RSV-B since those viruses are the most common pathogen found in respiratory tract. However, in order to gain optimal reaction for RSV-A and RSV-B detection, the optimization of primers and probes specific for RSV-A and RSV B are needed. Method: The primers and probes of multiplex rRT-PCR for RSV-A and RSV-B were selected and optimized utilizing PerlPrimer software and BLAST to analyze the secondary structures and specificity, respectively. Further testing of selected primers and probes for rRT-PCR was done using annealing temperature based on in silico analysis as mentioned above. This includes sensitivity testing with the utilization of synthesized DNA of RSV-A and RSV-B and specificity testing targeting the common viruses found in respiratory tract. Results: The primer set and probes selected for RSV-A and RSV-B detection were specific only for RSV-A and RSV-B and showed no secondary structure. Based on primer and probe criteria for rRT-PCR such as annealing temperature, no secondary structure formed, % GC content and limit of detection, the multiplex rRT-PCR test using selected primers and probes was able to detect synthesized DNA of RSV-A and RSV-B. Conclusion: Multiplex rRT-PCR that employing primer sets and probes targeted N gene of RSV-A and RSV-B in this study were able to be detect RSV-A and RSV-B in single PCR reaction. Keyword: Multiplex, real-time RT-PCR, RSV-A, RSV-B Abstrak Latar belakang: Multiplex real-time RT-PCR (rRT-PCR) merupakan metode yang cepat, sensitif dan spesifik untuk mendeteksi lebih dari satu target pathogen dalam satu reaksi PCR. Penelitian ini bertujuan untuk mengembangkan multiplex rRT-PCR virus RSV-A dan RSV-B yang merupakan patogen yang paling sering ditemukan di saluran pernafasan. Optimisasi dari primer dan probe dalam multiplex rRT-PCR diperlukan untuk mendapatkan reaksi yang optimal dalam deteksi virus RSV-A dan RSV-B. Metode: Primer dan probe untuk multiplex rRT-PCR RSV-A dan RSV-B dipilih dan dioptimasi menggunakan software PerlPrimer dan BLAST untuk menganalisis adanya struktur sekunder serta spesifisitas dari primer dan probe. Uji multiplex rRT-PCR dilanjutkan berdasarkan suhu annealing berdasarkan hasil analisis menggunakan PerlPrimer. Uji sensitifitas dilakukan dengan menggunakan DNA sintetis dari RSV-A dan RSV-B dan uji spesifisitas dilakukan dengan mengetes primer dan probe terhadap virus-virus lain yang umumnya ditemukan di saluran pernafasan. Hasil: Primer dan probe yang dikembangkan pada penelitian ini tidak membentuk struktur sekunder dan spesifik mengamplifikasi hanya RSV-A dan RSV-B. Berdasarkan kriteria primer dan probe untuk digunakan dalam rRT-PCR yaitu suhu annealing, tidak adanya pembentukan struktur sekunder, % GC content serta detection limit, uji multiplex rRT-PCR yang dikembangkan pada penelitian ini mampu mendeteksi DNA sintetis RSV-A dan RSV-B. Kesimpulan: Multiplex rRT-PCR dengan menggunakan primer dan probe untuk RSV-A dan RSV-B dapat mendeteksi RSV-A dan RSV-B dalam satu reaksi PCR. Kata kunci: multiplex, real-time RT-PCR, RSV-A, RSV-B